Charlie Brown's super book of things to do and collect : based on the Charles M. Schulz characters. - Schulz, Charles M. (Charles Monroe), 1922-2000 (Random House, 1975)
The Peanuts characters guide the beginning collector in starting, storing, and displaying collections and give instructions for making a variety of associated projects.